Experimental study on combustion characteristics of powder magnesium and carbon dioxide in rocket engine. (February 2019) - Li, Yue; Hu, Chunbo; Zhu, Xiaofei; Hu, Jiaming; Hu, Xu; Li, Chao; Cai, Yupeng
Abstract: Mechanisms of powder magnesium and carbon dioxide combustion are required for the concept of Mars propulsion based on the perspective of in-situ resource utilization. Most current characterizations are based on laboratory experiments conducted in stationary or simple flow configuration. However, the chamber condition in most applications of engine is very complicated with high pressure and multi-phase flow environment, and the combustion process in engine-scale has not been established. The burning efficiency, combustion stability and excessive deposition are the mainly primary issues that limit the combustion performance in rocket environment, the experimental study aims at combustion characteristics and the affection mechanism of powder magnesium and carbon dioxide in rocket engine. A new configuration of powder rocket system is established. Meanwhile, a multiple-inlet configuration of CO2 injection is designated to control the CO2 injection positions and parameters, such as global and local oxidant-fuel ratio. Ignition process is studied and an empirical model for ignition judgment is established according to the result of ignition tests. Mechanism for combustion deposition is studied by the analysis of morphology, composition and distribution, characteristics of combustion efficiency are estimated based on test pressure and thermodynamic calculation, and oscillation mechanism of combustion pressure is obtained by frequency domain analysis. The higher concentration of magnesium particle, the cool CO2 injection and the increasing of CO concentration is supposed to be the main reasons for the deposition in different areas along the axis of the combustion chamber. The allocation of gas injection is an important factor that affects the combustion sufficiency associated to the heterogeneous reaction. Raising the O/F ratio in chamber head is an effective way to improve combustion efficiency for rocket engine, and the efficiency is improved firstly and then is decreased with increasing flow rate of fluidization gas. The low frequency oscillation is supposed to be related to flame instability induced by the gas injection in chamber head. The influence caused by primary and secondary gas injection are further analyzed in the frequency domain, the related characteristic bands are classified and the fluctuation tendency is obtained. Graphical abstract: Image 1 Highlights: Highlights of Experimental Study on Combustion Characteristics of Magnesium and Carbon Dioxide in Powder Rocket Environment: Combustion investigation of magnesium and carbon dioxide in engine-scale Powder combustion based on in-situ resource utilization for Mars exploration Multiple gas injection configuration for combustion chamber of prototype rocket Analysis of combustion efficiency and stability by fire experiment Deposition characteristics and mechanism in combustion chamber